2020
DOI: 10.22146/ae.57396
|View full text |Cite
|
Sign up to set email alerts
|

Did The Program Kampung Iklim Lead Farmers to Implement more Adaptation Strategies? Case Study of Rice Farmers in Sleman Regency

Abstract: The negative impacts of climate change caused many losses for farmers. One solution to minimize losses is to implement a climate change adaptation strategy. The Indonesian government established a program called the Program Kampung Iklim/Proklim in 2012 which aims to increase awareness of climate change and the capacity to implement community adaptation strategies. This study aimed to determine the effect of the Proklim on the implementation of climate change adaptation strategy by farmers. The study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Based on the results of the research above, it can be concluded that in addition to several successful implementations of Proklim in a number of regions (Muttaqin et al, 2019) (Qomariah et al, 2021) (Priyanto et al, 2020), the study also found various challenges, especially the response of the community in carrying out the Proklim. Mainly related to community involvement in adaptation or how people find solutions to climate change and environmental damage caused by a changing climate that affects their ability to meet their daily needs.…”
Section: The Current Development Of Proklimmentioning
confidence: 94%
“…Based on the results of the research above, it can be concluded that in addition to several successful implementations of Proklim in a number of regions (Muttaqin et al, 2019) (Qomariah et al, 2021) (Priyanto et al, 2020), the study also found various challenges, especially the response of the community in carrying out the Proklim. Mainly related to community involvement in adaptation or how people find solutions to climate change and environmental damage caused by a changing climate that affects their ability to meet their daily needs.…”
Section: The Current Development Of Proklimmentioning
confidence: 94%
“…The cultivated land area is one of the most influential forms of capital. As a result, farmers with more land tend to employ the strategy more extensively (Priyanto et al 2020).…”
Section: Climate Change Adaptation Strategymentioning
confidence: 99%
“…Climate change's adverse effects on agriculture spur innovation to adapt to environmental changes. Farmers must adapt their cultivation practices to climate change to minimize losses due to reduced production (Priyanto et al 2020). The ultimate goal is to ensure that food is available to the population at all times (Campbell et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies about ProKlim in Indonesia had reported that ProKlim has positive impacts on environmental, social, and economic [41][42][43][44]. It is reported that ProKlim has succeeded embellish the community environment by their planting flowers and vegetable program.…”
Section: Opportunitymentioning
confidence: 99%